Gallium containing bioactive materials: A review of anticancer, antibacterial, and osteogenic properties - Fatih Kurtuldu; Nurshen Mutlu; Aldo R. Boccaccini; Dušan Galusek (Bioactive Materials, 2022)
The incorporation of gallium into bioactive materials has been reported to enhance osteogenesis, to influence blood clotting, and to induce anti-cancer and anti-bacterial activity. Gallium-doped biomaterials prepared by various techniques include melt-derived and sol-gel-derived bioactive glasses, calcium phosphate bioceramics, metals and coatings. In this review, we summarize the recently reported developments in antibacterial, anticancer, osteogenesis, and hemostasis properties of Ga-doped biomaterials and briefly outline the mechanisms leading to Ga biological effects. The key finding is that gallium addition to biomaterials has great potential for treating bone-related diseases since it can be efficiently transferred to the desired region at a controllable rate. Besides, it can be used as a potential substitute for antibiotics for the inhibition of infections during the initial and advanced phases of the wound healing process. Ga is also used as an anticancer agent due to the increased concentration of gallium around excessive cell proliferation (tumor) sites. Moreover, we highlight the possibility to design different therapeutic approaches aimed at increasing the efficiency of the use of gallium containing bioactive materials for multifunctional applications.